The aged require attention - J. Brawley (AOSIS, 1983)
Hospitals are institutions and people entering are treated as part of the whole. Nurses do things for patients and if they are too slow they are hurried up. The ward has a fairly rigid routine. It is all abnormal, yet under these circumstances people are expected to recover from illnesses, diseases and operations. Before they start to recover they have to learn to adapt to a physical and psychological environment which is quite unfamiliar to them. The younger you are the more easy it is to adapt because you are less set in your ways.